Efficacy of Intercostal Nerve Block for Pain Control After Percutaneous Nephrolithotomy: A Systematic Review and Meta-Analysis - Chen, Tao; Zhu, ZhenQiang; Du, Jianlong (Frontiers in Surgery, 2021)
Background: We aimed to assess the efficacy of intercostal nerve block (ICNB) for pain relief after percutaneous nephrolithotomy (PCNL). Methods: An electronic search of the databases of PubMed, Science Direct, BioMed Central, CENTRAL, Embase, and Google Scholar was conducted. All types of studies conducted on adult patients undergoing PCNL, comparing ICNB with control or any other anesthetic method, and reporting postoperative pain outcomes were included. Results: Six studies were included. Studies compared ICNB with peritubal (PT) infiltration and with control. Pooled analysis of ICNB vs PT infiltration indicated no difference between the two groups for pain scores at 6-8 hours (MD -0.44; 95% CI -3.41, 2.53; I2=99%; p=0.77), 12 hours (MD -0.98; 95% CI -4.90, 2.94; I2=99%; p=0.62) and 24 hours (MD 0.16; 95% CI -0.90, 1.21; I2=88%; p=0.77). Time for first analgesic demand was also not significantly different between the two groups. Meta-analysis of ICNB vs control indicated statistical significant difference in pain scores between the two groups at 8 hours (MD -1.55; 95% CI -2.60, -0.50; I2=47%; p=0.04), 12 hours (SMD -2.49; 95% CI -4.84, -0.13; I2=96%; p=0.04) and 24 hours (SMD -1.22; 95% CI -2.12, -0.32; I2=88%; p=0.008). The total analgesic requirement in morphine equivalents was not significantly different between the two groups. Conclusions: ICNB may be effective in reducing postoperative pain after PCNL. However, its efficacy may not be greater than PT infiltration. Current evidence is from a limited number of studies. Further, high-quality randomized controlled trials are needed to provide robust evidence.